PENERAPAN TEKTONIKA ARSITEKTUR YB. MANGUNWIJAYA DALAM PERANCANGAN RUMAH TINGGAL EMHA AINUN NADJIB - Rembulan, Lintang; Hardiyati, Hardiyati; Mustaqimah, Ummul (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Emha Ainun Nadjib’s house representation of human body make an effort for harmonizing public and private space, as well as the balance of human body’s appearance and function. The concept of fairness and honesty of Cak Nun’s house resolved through tectonic architecture of YB. Mangunwijaya that concern on exposing construction, lightweight structure, small building mass and the principle of locality. Cak Nun’s house as also a cultural center where people doing arts and spiritual activism so the building should give an inspiration and good effect for the environment and society. The principle of locality affect the use of structure and building construction, form and building orientation also the use of renewable material. The material used are bamboo, coconut wood, stone, clay and straw. Key words: YB. Mangunwijaya tectonic architecture, Emha Ainun Nadjib’s house, Bamboo, Coconut wood, Stone, Clay, Straw.